Effects of oral nutritional supplements plus mature silkworm pill on cognitive function in Korean adults with mild cognitive impairment: a 12-week randomized blinded clinical trial - Kim, Min Ji; Lee, Sun Min; Sun, Kyunghwa; Kim, Yeon Hee; Seo, Ye Jin; Park, Sun Ah; Park, Hyoung Su; Kim, Hye-Jin; Park, Yoo Kyoung; Moon, So Young (Frontiers in Nutrition, 2025)
ObjectiveThis study aimed to determine whether mature silkworm pills plus commercial oral nutritional supplements (ONS) could improve cognitive function, especially in individuals with mild cognitive impairment (MCI).MethodsA total of 62 participants (70.6 ± 8.5 years, 48.4% female), aged ≥50 years diagnosed with mild cognitive impairment but not dementia, were randomly assigned into the 12-week ONS plus silkworm pill group (30 participants, commercial ONS with mature silkworm pills) or the placebo group (32 participants, placebo ONS containing protein, carbohydrates, and fats, with placebo pills containing dextrin). During the 12-week intervention, participants consumed the allocated pills and ONS once daily. Additionally, nutritional education related to the Mediterranean-DASH Intervention for Neurodegenerative Delay (MIND) diet therapy and proper eating habits was provided at weeks 0, 3, 6, and 9. The primary outcome was interval change in the Korean version of the Repeatable Battery for the Assessment of Neuropsychological Status (K-RBANS) after the 12-week intervention. Secondary outcomes included interval changes in nutrient intake, nutrition-related blood test results, nutritional quotient, and MIND score evaluation.ResultsAfter 12 weeks, the interval change in the delayed memory domain score of the K-RBANS was improved in the ONS plus silkworm pill group (65.9 ± 19.0 vs. 70.5 ± 19.0, p = 0.011), and there was also a difference between the intervention and control groups (p = 0.018). The interval changes in the total scale and other cognitive domain scores of the K-RBANS were not statistically significant. There were no significant differences in the pre- and post-comparison results between the placebo and ONS plus silkworm pill groups in terms of other secondary outcomes, including nutrition-related blood test results, nutritional quotient, and MIND score.ConclusionAfter the 12-week intervention, the ONS and silkworm pill group showed a significant improvement in delayed memory compared with the placebo group. However, no significant differences were observed in other cognitive domains or secondary outcomes, such as nutrient intake, blood test results, nutrition quotient, or MIND score adherence. These findings suggest that, while the combination may have a positive impact on specific cognitive functions, further research is needed to fully understand its potential benefits and mechanisms of action.Clinical Trial Registrationhttps://trialsearch.who.int/Trial2.aspx?TrialID=KCT0007304.